Three Italian practitioners seeking a more popular audience for Shakespeare (Altre Modernità, 2017)
My contribution, "Seeking a More Popular Audience for Shakespeare in Italy", starts by pinpointing the differences between Italy and the UK in the history of the staging of Shakespeare's plays and goes on to provide a brief account of the evolution of Shakespeare productions in Italy from the 1950s until the present. In the aftermath of World War Two, the so-called critical direction (regia critica) introduced a very different approach to the staging of Shakespeare. Directors, such a Giorgio Strehler and Luigi Squarzina, by commissioning new Italian translations that were philologically close to the originals, put the complete plays onstage, often for the first time. In a long career at Milan's Piccolo Teatro, spanning from the late 1940s until his death in 1997, Strehler succeeded in attracting a more mixed audience for Shakespeare than ever before. In the new millennium, his aims have been taken further by more recent practitioners. The final part of the contribution focuses on three contemporary Italian directors, Marco Ghelardi, Riccardo Mallus and Massimo Navone, who seek to bring Shakespeare to more popular audiences. In a bid to energise the Bard's work, they deploy strategies, such as reducing and rewriting the play, interactive staging techniques and tend to choose site specific venues rather than regular theatres.